Human Resources and Digital Transformation in Education: Driving Innovation and Sustainability - Reyhana Nur Azizah; Sofia Nisa Ulyantika; Melyna Wijaya Putri; Junaidah Junaidah; Septuri Septuri (Universitas Nurul Jadid, 2026)
This research is motivated by the increasing need for educational institutions to carry out digital transformation effectively, while its success is still highly dependent on the readiness of human resources. This research aims to analyze the role of teachers, education staff, and school managers in encouraging innovative and sustainable digital transformation in schools. The research uses a qualitative, case-study approach. Data is collected through semi-structured interviews, observations, and documentation, then analyzed through data condensation, data reduction, data presentation, and verification. The study's results show that digital transformation is effective when human resources possess digital literacy, pedagogical awareness, adaptability, and institutional support. The use of LMS, e-learning, interactive media, and AI is not even necessary, as there are still differences in competencies among educators. In conclusion, technology cannot be the main driver of change without adequate human capacity. Theoretically, these findings expand the study of digital education management by placing human resources at the center of innovation success, rather than just technology users. This research contributes to strengthening the human-centered perspective on digital transformation in education and provides a practical basis for developing continuing education innovations in modern Islamic boarding school-based schools.